Dragonetti, Carmen and Fernando Tola, On the Myth of the Opposition between Indian Thought and Western Philosophy, Hildesheim-Zürich-New York, Georg Olms Verlag, 2004, 293 pp - Rollié, Emilio Federico (2005)
Fil: Rollié, Emilio Federico. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.